Evaluation of interfraction setup variations for postmastectomy radiation therapy using EPID‐based in vivo dosimetry. Issue 10 (21st September 2019) - Kang, Shengwei; Li, Jie; Ma, Jiabao; Zhang, Wei; Liao, Xiongfei; Qing, Hou; Tan, Tingqiang; Xin, Xin; Tang, Bin; Piermattei, Angelo; Orlandini, Lucia Clara
Abstract: Postmastectomy radiation therapy is technically difficult and can be considered one of the most complex techniques concerning patient setup reproducibility. Slight patient setup variations — particularly when high‐conformal treatment techniques are used — can adversely affect the accuracy of the delivered dose and the patient outcome. This research aims to investigate the inter‐fraction setup variations occurring in two different scenarios of clinical practice: at the reference and at the current patient setups, when an image‐guided system is used or not used, respectively. The results were used with the secondary aim of assessing the robustness of the patient setup procedure in use. Forty eight patients treated with volumetric modulated arc and intensity modulated therapies were included in this study. EPID‐based in vivo dosimetry (IVD) was performed at the reference setup concomitantly with the weekly cone beam computed tomography acquisition and during the daily current setup. Three indices were analyzed: the ratio R between the reconstructed and planned isocenter doses, γ % and the mean value of γ from a transit dosimetry based on a two‐dimensional γ ‐analysis of the electronic portal images using 5% and 5 mm as dose difference and distance to agreement gamma criteria; they were considered in tolerance if R was within 5%, γ % > 90% and γ mean  < 0.4. One thousand and sixteen EPID‐based IVD were analyzed and 6.3% resulted out of the tolerance level. Setup errors represented the main cause of this off tolerance with an occurrence rate of 72.2%. The percentage of results out of tolerance obtained at the current setup was three times greater (9.5% vs 3.1%) than the one obtained at the reference setup, indicating weaknesses in the setup procedure. This study highlights an EPID‐based IVD system's utility in the radiotherapy routine as part of the patient's treatment quality controls and to optimize (or confirm) the performed setup procedures' accuracy.